Effects of adolescent nicotine exposure and withdrawal on intravenous cocaine self-administration during adulthood in male C57BL/6J mice - Dickson, Price E. (2012)
Studies of adolescent drug use show (1) a pattern in which the use of tobacco precedes the use of other drugs and (2) a positive relationship between adolescent tobacco use and later drug use. These observations have led to the hypothesis that a causal relationship exists between early exposure to nicotine and the later use of hard drugs such as cocaine. Using male C57BL/6J mice, we tested the hypothesis that nicotine exposure in adolescence leads to increased intravenous self-administration (IVSA) of cocaine in adulthood. Using miniature osmotic pumps, we exposed mice and their littermate controls to nicotine (24 mg/kg/day) or vehicle, respectively, over the entire course of adolescence [postnatal days (P) 28–56]. Nicotine exposure was terminated on P56 and mice were not exposed to nicotine again during the experiment. On P73, mice were allowed to acquire cocaine IVSA (1.0 mg/kg/infusion) and a dose–response curve was generated (0.18, 0.32, 0.56, 1.0, 1.8 mg/kg/infusion). Lever pressing during extinction conditions was also evaluated. All mice rapidly learned to lever press for the combination of cocaine infusions and non-drug stimuli. Analysis of the dose–response curve revealed that adolescent nicotine-exposed mice self-administered significantly more (P < 0.05) cocaine than controls at all but the highest dose. No significant differences were observed between adolescent nicotine-exposed and control mice during the acquisition or extinction stages. These results indicate that adolescent nicotine exposure can increase cocaine IVSA in mice, which suggests the possibility of a causal link between adolescent tobacco use and later cocaine use in humans.